2002
DOI: 10.1556/amicr.49.2002.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of antibodies to Hepatitis A and E viruses in pediatric age groups in Turkey

Abstract: Hepatitis A and hepatitis E are enteric transmitted viral diseases occurring in epidemic and sporadic forms especially in developing countries. Previous studies in Turkey showed that most residents are infected with HAV by the second decade of life. Since HEV is generally transmitted by the same route as HAV we conducted a community-based seroprevalence study for HAV and HEV infection in Ahatli area in Antalya, Turkey where socioeconomic conditions are low. Anti-HAV total immunoglobulin was tested by using a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
3
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 20 publications
1
21
3
5
Order By: Relevance
“…This is in keeping with the findings of Colak et al [15] and Aggarwal et al [20], who showed that intrafamilial transmission of HEV was rare. This could be due to the fact that there is a low level of fecal secretion of HEV [20], and so intrafamilial or personto-person transmission is low.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in keeping with the findings of Colak et al [15] and Aggarwal et al [20], who showed that intrafamilial transmission of HEV was rare. This could be due to the fact that there is a low level of fecal secretion of HEV [20], and so intrafamilial or personto-person transmission is low.…”
Section: Discussionsupporting
confidence: 92%
“…This rather lower value in rural Ghana may be due to variation in the sensitivity of the immunoassay kits in different laboratories. Colak et al [15] found a prevalence rate of 0.9% in children in Turkey. Turkey is a country in the European Union, and socioeconomic conditions there are better than those in the community where this study was done.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, the HEV seropositivity was found to be higher in children aged seven years compared to children aged 14 years (13). In a study conducted in the province of Antalya in our country, HEV antibody was not found in any child in preschool children, whereas the prevalence of anti-HEV IgG was found to be 1.6% in school age children (14). In another study conducted in our country, the HEV seropositivity was found to be 0% in children aged between 0 and 5 years and it was reported that the seropositivity rate increased as the age advanced (6).…”
Section: Discussioncontrasting
confidence: 46%
“…Currently available commercial serological assays are based on genotype 1 and 2 antigens and might have lower sensitivity for detection of infections with the genotype 3 strains (4,6,18). In addition, the positive predictive value is lower in areas of low endemicity (like The Netherlands) than in the countries of where it is endemic, due to the low overall seroprevalence.…”
mentioning
confidence: 99%